Gastric Cancer: The Role of Diffusion Weighted Imaging in the Preoperative Staging. (28th May 2014) - Caivano, R.; Rabasco, P.; Lotumolo, A.; D' Antuono, F.; Zandolino, A.; Villonio, A.; Macarini, L.; Guglielmi, G.; Salvatore, M.; Cammarota, A.
<x xml:space="preserve">Abstract</x> Purpose: Evaluate the role of diffusion-weighted-imaging (DWI) in the diagnosis and staging of gastric carcinoma. Materials and methods: A total of 31 patients with gastric adenocarcinoma, which underwent preoperative staging with 3Tesla Magnetic Resonance Imaging (MRI), were enrolled. Two radiologists evaluated the tumor staging in DWI. Results were compared to postsurgical pathologic findings. Results: The T factor accuracy of conventional MRI and DWI was 73% and 80% respectively; while the N staging accuracy of conventional MRI and DWI was 80% and 93%, respectively. Conclusion: DWI and apparent diffusion coefficient (ADC) values showed to be useful in preoperative staging of gastric cancer.